2022
DOI: 10.3390/s22155469
|View full text |Cite
|
Sign up to set email alerts
|

Smart Insole Based on Flexi Force and Flex Sensor for Monitoring Different Body Postures

Abstract: This study aims to fabricate smart insoles using wireless Flexi force and bend sensing technology. Polyvinyl chloride (PVC) film was chosen as the substrate to hold all the sensors. The developed smart insole has a three-layer structure (insole-PVC layer-fabric layer) and is calibrated in an isolation laboratory to evaluate its measurement performance. One male volunteer subject exhibited four different body postures, namely tree pose, forward-leaning, squatting, and forward folding pose. Changes in pressure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…The highest value of nanogenerators' voltage outputs measured during walking was 41 V. It has also been possible to recognize differences in different speeds and limp walking performed during the experiment through the multiscale entropy analysis of stride intervals. Some other authors [94] proposed a smart insole to monitor other body postures, using four wireless Flexi force sensors and a flex sensor embedded within the insole, made of Polyvinyl Chloride. Results from this study, where four different body positions (tree, leaning forward, squat, and forward fold postures) were performed by a subject, showed that the feet pressure measured through the insoles changed during each body posture modification, growing on the first, fifth, and third metatarsals.…”
Section: Smart Insoles In Human Gait and Posture Analysismentioning
confidence: 99%
“…The highest value of nanogenerators' voltage outputs measured during walking was 41 V. It has also been possible to recognize differences in different speeds and limp walking performed during the experiment through the multiscale entropy analysis of stride intervals. Some other authors [94] proposed a smart insole to monitor other body postures, using four wireless Flexi force sensors and a flex sensor embedded within the insole, made of Polyvinyl Chloride. Results from this study, where four different body positions (tree, leaning forward, squat, and forward fold postures) were performed by a subject, showed that the feet pressure measured through the insoles changed during each body posture modification, growing on the first, fifth, and third metatarsals.…”
Section: Smart Insoles In Human Gait and Posture Analysismentioning
confidence: 99%
“…This part of the vertebra will provide support and base for the movement of head and neck. This region is branched up with different group of muscles that provide mechanical strength and locomotion of the neck [11][12][13][14]. Data acquisition The data is acquired at a time interval of every 70 seconds.…”
Section: Design Module a Sensor Placement Sensor Placement In Neckmentioning
confidence: 99%